PENGEMBANGAN MODUL AJAR MATERI PERKALIAN BERBASIS PENDEKATAN CONCRETE-PICTORIAL-ABSTRACT (CPA) UNTUK MENINGKATKAN LITERASI NUMERASI SISWA SEKOLAH DASAR - Faza Shafira, - (2022)
module of Concrete-Pictorial-Abstract (CPA)-based multiplication material to improve the numeracy literacy of elementary school students. This research was motivated by students are in an unstable position in defining the concept of multiplication because the learning method focuses on memorization and only comes from the teacher and source books. So that, students' numeracy literacy is low, with a percentage of 28% of students in one class who get scores above 70. The research method used is Design and Development (D&D) proposed by Richey and Klein with Planning, Production, Evaluation (PPE) procedures. The elegibility of the teaching module was validated by three experts, namely a material expert, a design expert, and a linguist. The validation results from material experts get a 95% eligibility and included in the excellent criteria. The validation results from design experts get a percentage of 89% and are included in the very good criteria. The validation results from linguists get a percentage of 92.5% and are included in the very good criteria. The total validation results from the three experts got 92.167% and included in the excellent category. In addition, a limited trial was conducted on 7 people from 3rd grade elementary school students. Limited trials were conducted to test product readability and test students' literacy skills. The results of the students' literacy ability test which were carried out through the pretest and posttest obtained the average value of the students' pretest results, while the average posttest results were 83. It can be seen that the average value of the posttest results was greater and significantly different from the pretest score (83 > 50).